2014
DOI: 10.1002/ett.2843
|View full text |Cite
|
Sign up to set email alerts
|

Capacity analysis of power line communication point‐to‐point and relay channels

Abstract: In this paper, we present a capacity analysis for broadband power line communication (PLC) channels, impaired by the Bernoulli-Gaussian impulsive noise, exploiting both orthogonal frequency division multiplexing (OFDM) and singlecarrier frequency-domain equalisation (SC-FDE) techniques. First, we investigate point-to-point communications and formulate the continuous signal model for OFDM and SC-FDE techniques in PLC environments and find the tight bounds derived for differential entropy of the non-Gaussian noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…It shows that, as the coherence bandwidth increases with the frequency, the DS decreases. The channel capacity in broadband PLC was analysed and presented by Sheikh‐Hosseini et al and Anatory et al It indicates that the channel capacity varies with the voltage level and with the environment. For example, for a PSD between −90 and −30 dBm/Hz, the channel capacity decreases by 20‐30 Mbps per branch, 14‐24 Mbps per branch, and 20‐25 Mbps per branch for a medium‐voltage, a low‐voltage, and an indoor channel, respectively.…”
Section: Quick View Of Plc and Vlc Channels And Modelsmentioning
confidence: 99%
“…It shows that, as the coherence bandwidth increases with the frequency, the DS decreases. The channel capacity in broadband PLC was analysed and presented by Sheikh‐Hosseini et al and Anatory et al It indicates that the channel capacity varies with the voltage level and with the environment. For example, for a PSD between −90 and −30 dBm/Hz, the channel capacity decreases by 20‐30 Mbps per branch, 14‐24 Mbps per branch, and 20‐25 Mbps per branch for a medium‐voltage, a low‐voltage, and an indoor channel, respectively.…”
Section: Quick View Of Plc and Vlc Channels And Modelsmentioning
confidence: 99%
“…By assuming that the noise state information is known at both transmitter and receiver terminals, the capacity of Middleton class A noise channel has been calculated in the study of Wiklundh et al Mutual information of BG noise channels has been bounded from both sides by Gaussianity assumption for the channel input and output in the works of Herath et al and Vu et al Under an average power constraint in the works of Vu et al, and Le et al, it was demonstrated that the capacity‐achieving input distribution of GM noise channels must be discrete with a finite number of mass points. Finally, in the study of Sheikh‐Hosseini et al, the bounds of differential entropy and capacity have been computed for the broadband point‐to‐point and relay PLC channels impaired by BG noise.…”
Section: Introductionmentioning
confidence: 99%
“…A parallel relay network is considered in [19] in which data rate maximization is analyzed. Using a pair of transmitter-receiver and single antenna as a relay, peer-to-peer communication is analyzed in [20,21]. Joint iterative power allocation and interference cancellation in spread spectrum networks is presented in [22] in which multiple hops and the amplify-and-forward (AF) relaying strategy are applied for both uplink and downlink.…”
Section: Introductionmentioning
confidence: 99%